Structural behavior analysis of a continuous steel truss arch railway bridge integrating monitoring data - Yong-sheng Song; You-liang Ding; Han-wei Zhao; Gao-xin Wang; Ai-qun Li; Bao-ya Cao (Advances in Mechanical Engineering, 2016)
Using theoretical modeling combined with monitoring data, the typical dynamic and static behaviors of a continuous steel truss arch railway bridge are evaluated. The dynamic behavior involves an impact factor induced by the action of running trains, and the static behavior refers to axial bending performance and the stress distribution among different planes of the truss. The transverse position, length, and speed of running trains are introduced to conduct an analysis of their influences on the dynamic and static behaviors of the bridge superstructure. A structural safety evaluation is also conducted by comparison with the provisions recommended by design codes and by analysis of absolute stress. It is concluded that three types of members present different dynamic behaviors and that the value of the impact factor for chords B exceeds the provision recommended by the design codes. Chords C present the greatest ratio of bending stress versus axial stress. An imbalance of stress distribution exists among the three planes of the truss, and the difference is the smallest when trains run along the middle railways. Because the train-induced stress is considerably lower, the dynamic and static performances of the bridge are within the scope of safety.